Pendidikan Kesehatan Dalam Meningkatkan Pengetahuan Siswa SMK 45 Lembang Tentang Pencegahan Hepatitis - Theophylia Melisa Manumara; Reggy Ramadhani; Salsa Manda Aulia Fasya; Elsa Lestari; Tiara Nur Agustin; Shearlie Sriayu Diah Azahra; Kartini Kartini; Cici Lestari; Reva Oktavia Ramadhani; Mohamad Ihsan Pahlevi; Amanda Nabillatussahara Ramadani (Jurnal Medika: Medika, 2026)
Hepatitis is an inflammation of the liver that has become a global health issue with persistently high incidence and mortality rates. This disease can be caused by viral infections, unhealthy lifestyles, or exposure to toxic substances, and often progresses without symptoms, earning it the nickname “the silent killer.” The lack of public awareness, particularly among adolescents, regarding the transmission and prevention of hepatitis is a key reason for conducting health education activities at SMK 45 Lembang. This activity aims to improve students’ understanding of hepatitis, covering its definition, symptoms, modes of transmission, prevention, and the implementation of Clean and Healthy Living Behaviors (PHBS). The method used in this community service initiative was health education through lectures and interactive discussions with 30 students at SMK 45 Lembang. The material was delivered using educational media and question-and-answer sessions to increase participant engagement. The results of the activity showed an increase in students’ knowledge and understanding of the importance of maintaining liver health, practicing personal hygiene, and avoiding risky behaviors that can lead to hepatitis transmission. In conclusion, health education on hepatitis is effective in raising students’ awareness and promoting preventive behaviors as part of efforts to prevent the disease and break the chain of hepatitis transmission within the school and community.